Does eradication of Helicobacter pylori infection reduce hypergastrinema during long term therapy with proton pump inhibitors? - Ahmet K. GÜRBÜZ,; Yaşar KÜÇÜKKARDALI,; Yusuf YAZGAN,; Melih ÖZEL,; Taner POLAT, (Turkish Journal of Gastroenterology, 2019)
-